Pragmatic Study of Discourse Hegemony on the Enactment of Dhalang Trah in Ruwatan Ceremony: A Critical Discourse Analysis Approach - Efendi, Agus; Purwasito, Andrik; Sudardi, Bani; Abdullah, Wakit (Komunitas, 2016)
This study applies qualitative research with Critical Discourse Analysis (CDA) of Fairclough (1995) and the criticism on the ideological dissection of social opacities. The data collection encompasses the interactive and non-interactive techniques which involve the techniques of in-depth interviewing, observation and content analysis. Results of the analysis reveal that units of language use reflected from the texts and contexts of the ruwat puppeteer based genealogy's enactment can be traced from the use of modalities, the phrase ‘mboten kalilan’ (impermissible, unable) in the decree of dhalang ruwat can be further extend to express the word ‘unable’ and ‘able to’, other aspects such as politeness, metaphors, ethos which is classified into the verbal and non-verbal discourse are the devices of discursive enactment of the elite power of dhalang trah. The findings conclude that there is arising symptoms of social inequality narrowing the role and significance of the non-ruwat puppeteers. The hegemonic practice such as the discursive enactment of dhalang trah (descendent of Ki Lebdajiwa) is determined by certain associations which try to normalize certain condition. The argument which refers to the enactment of Ki Lebdajiwa and his descendants as the holder of power is enacted through transactional form, where power is centered on one point.